Learning Through Participation in Joint Management Committees for Reservoir-Level Irrigation Governance in Thailand - Walker, Heidi; Sinclair, A. John; Kumnerdpet, Wachiraporn (International Journal of Water Governance, 2015)
The UN indicates that water for irrigation and food production constitutes one of the greatest pressures on freshwater resources, especially within the Asian region. Recent developments in water management relate to participatory governance, where civil society is included in the political, social, economic, and administrative systems that develop and manage water resources. In Thailand, the Royal Irrigation Department has adopted Participatory Irrigation Management (PIM), which involves multiple sectors of water users in decision-making at all levels of irrigation system management. This research identified learning outcomes associated with participation in Joint Management Committees for Irrigation (JMC), the top PIM governance tier, particularly related to governance and sustainable water management. Our research was qualitative following a case study approach, utilising 51 semi-structured interviews at two sites, participant observation, and document reviews. Results showed that participating in PIM activities facilitated both instrumental (e.g. technical knowledge, skills and information, and task-based learning) and communicative (e.g. insights into the interests of others, communication strategies, and comparative reflection) learning among JMC participants. Findings also showed that action outcomes based on learning were mainly related to adopting new governance systems and conserving water for future irrigation use.